Analisis Terhadap Pemotongan Dan Pemungutan Serta Pelaporan Pajak Penghasilan Pasal 23 Atas Jasa Outsourcing Pada PT. CIMB Niaga Auto Finance - Dede Mulyadi; Nurwati Nurwati (ITB Ahmad Dahlan Jakarta, 2019)
Tax is one source of state revenue. One source of tax revenue is income tax article 23 for outsourcing services. The purpose of this study was to find out and analyze the deduction and collection as well as income tax report article 23 for outsourcing services at PT CIMB Niaga Auto Finance in accordance or not in accordance with Law PPh Number 36 of 2008. This research is descriptive qualitative because it only uses exposures from the facts obtained at the research site. The results of this study, namely the implementation of the deduction and collection and reporting of income tax article 23 for outsourcing services at PT CIMB Niaga Auto Finance has been running optimally in accordance with Law Number 36 of 2008 concerning Income Tax.